Infrastructure & governance - Kochhar, Sameer (New Delhi : Academic Foundation, 2008)
Contributed articles with reference to India; emanating from a seminar organised by Skoch Consultacy Services on 17-18 October, 2007 at New Delhi, India.
Keywords: Infrastructure (Economics) -- India; Internet in public administration -- India